Karyological notes on eight species of Achillea L. (Asteraceae, Santolinoideae) from Turkey - Sahin, Ahmet; Kiran, Yasar; Arabaci, Turan; Turkoglu, Ismail (Oxford Univ Press, 2006)
The chromosome number and morphology of eight species belonging to the section Santolinoideae of the genus Achillea L. (Asteraceae) were investigated using karyological techniques. The species studied were Achillea cucullata (Hausskn.) Bornm., A. vermicularis Trin., A. monocephala Boiss. & Bal., A. boissieri (Hausskn.) Bornm., A. santolina L., A. gypsicola Hub.-Mor., A. goniocephala Boiss. & Bal., and A. spinulifolia Fenzl ex Boiss. In these species, the chromosome numbers were 2n = 18 in A. vermicularis, A. monocephala, and A. boissieri, 2n = 18A + 1B in A. spinulifolia, 2n = 36 in A. cucullata and A. santolina, and 2n = 54 in A. gypsicola and A. goniocephala. All of the chromosomes had median point (M), median region (m), or submedian (sm) centromeres. An increase in asymmetry was not observed in the karyotypes of the species. (c) 2006 The Linnean Society of London.
Keywords: chromosome number; karyotype; mitosis